Transformasi Pelaporan Insiden Keselamatan Pasien melalui SIPANDU Digital di RSU Ja’far Medika - Muhlizardy Muhlizardy; Aslam Adzkia Al-Qudsi; Niken Widya Saputri (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2026)
Patient safety is a fundamental aspect of hospital services; however, the incident reporting system at RSU Ja’far Medika has been manually operated, often resulting in delays and incomplete reporting. This Community Service Program (PkM) aimed to implement a Digital Integrated Patient Safety Incident Reporting System (SIPANDU) to enhance reporting efficiency and improve service quality. The program was carried out in two stages: (1) a needs analysis conducted through coordination meetings with the Head of IT and the Hospital Director, and (2) the implementation of SIPANDU, which was piloted within the hospital environment. The results showed that SIPANDU was successfully implemented without technical issues, enabling real-time, accurate, and easily accessible incident reporting. The outputs of this program included a comprehensive needs analysis document, a fully functional SIPANDU system, and improved hospital managerial capacity in patient safety monitoring. This implementation is expected to increase staff participation in incident reporting and foster a sustainable patient safety culture. The success of this program provides a replicable model for other hospitals in advancing digital transformation for patient safety.